The Effect of Xevinapant Combined with Ionizing Radiation on HNSCC and Normal Tissue Cells and the Impact of Xevinapant on Its Targeted Proteins cIAP1 and XIAP - Fleischmann, Julia; Hildebrand, Laura; Kuhlmann, Lukas; Fietkau, Rainer; Distel, Luitpold (Cells, 2023)
The poor prognosis of HNSCC is partly due to treatment resistance. The SMAC mimetic Xevinapant is a promising new approach to targeted cancer therapy. Xevinapant inhibits cIAP1/2 and XIAP, leading to apoptosis, necroptosis and inhibition of prosurvival signaling. Combining Xevinapant with IR could improve therapeutic potential. The effect of Xevinapant in combination with IR on HNSCC and healthy tissue cells was investigated. Cell growth, cell death, clonogenic survival and DNA double-strand breaks (DSBs) were studied, and intracellular cIAP1 and XIAP levels were evaluated. Xevinapant had cytostatic and cytotoxic, as well as radiosensitizing, effects on the malignant cells, while healthy tissue cells were less affected. Apoptotic and necrotic cell death was particularly affected, but the increase in residual DSBs and the reduced survival implied an additional effect of Xevinapant on DNA damage repair and other cell inactivation mechanisms. cIAP1 and XIAP levels varied for each cell line and were affected by Xevinapant and IR treatment. There was an association between higher IAP levels and increased cell death. Xevinapant appears to be a potent new drug for HNSCC therapy, especially in combination with IR. IAP levels could be an indicator for impaired DNA damage repair and increased susceptibility to cellular stress.
CRIS-Team Scopus Importer:2024-12-16
Keywords: apoptosis; cIAP1/2; head and neck squamous cell carcinoma; inhibitor; interactions; ionizing radiation; targeted therapy; Xevinapant; XIAP